ANALISIS PERSEPSI NASABAH TERHADAP STRATEGI PEMASARAN PADA LAYANAN BSI MOBILE (STUDI KASUS PADA NASABAH BANK SYARIAH INDONESIA KANTOR CABANG JAMBI) - Dessy Anggraini; Dewi Sartika (MARGIN: Journal of Islamic Banking, 2024)
The purpose of this research is to find out how customers perceive BSI Mobile Services at BSI KC Jambi and to find out their opinions regarding the marketing strategies implemented in providing BSI Mobile Services at BSI KC Jambi. This research uses a qualitative approach with interviews and documentation of 10 BSI KC Jambi customers. From the results of the research conducted, it is known that customer perceptions of the services provided by mobile banking are relatively good and the BSI mobile application is also very useful for customers. In this case, BSI Mobile emphasizes that the promotional strategy for the BSI Mobile application is setting prices for BSI Mobile Banking products based on customer perceptions, namely that the prices/costs offered by BSI Mobile remain according to standards.